Vejrforholdene i Landbrugsaaret 1885—80o: fra 1. Oktober 1885 til 30. September 1886. - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1885—80o: fra 1. Oktober 1885 til 30. September 1886.